EFEK SUMUR RESAPAN TERHADAP PENGURANGAN VOLUME LIMPASAN PERMUKAAN - I WAYAN YASA; SASMITO SOEKARNO; I DEWA GEDE JAYA NEGERA (GANEC SWARA, 2020)
Changes in land use not only affect the hydrological component, but also have an impact on the environmental sector, which include increasing the frequency of flooding and inundation, decreasing the availability of subsurface water, and drying up community wells. Various attempts have been made in efforts to reduce flooding and maintain sources of subsurface water, for example by applying infiltration well technology in each settlement. Infiltration wells will be able to function to re-enter rainwater falling on the pavement and can reduce flooding and inundation. This research is conducted with an empirical model that is connecting the amount of runoff that occurs after the availability of recharge wells. The purpose of this research is to get the ability of infiltration wells to reduce the occurrence of flooding in an area. The data used in the analysis are rain data and soil texture data. Based on the analysis results obtained dimensions of 0.8 m, 1 m and 1.2 m infiltration wells with a depth of 2 m. The depth of ground water level is 1.94 m, the permeability value (k) of land is 0.24 x 10ˉ⁴ m / sec. From each of the infiltration well diameters, it can reduce the successive runoff namely; infiltration wells are 0.8 m in diameter from runoff of 0.479 m³ / sec and after an infiltration well is reduced to 0.057m³ / sec, infiltration wells diameter 1.2 from runoff is 0.401 m³ / sec and after an infiltration well is reduced to 0.0475 m / second, and in the diater infiltration well 2 m from runoff of 0.377 m³ / sec and after the infiltration well is reduced to 0.0571 m / sec.